PENYUSUNAN RAB RENOVASI MASJID AL-HASANAH DI KEL. KREO SELATAN, KEC. LARANGAN KOTA TANGERANG - Inggit Musdinar Sayekti Sihing Yang Mawantu; Dody Kurniawan; Suwasti Broto (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The mosque is a place of worship for Muslims. The Ministry of Religion issued provisions regarding different designations for mosques. One of the prayer rooms in Kelurahan Kreo Selatan is the Al-Hasanah Mosque which is located at Gang Sawo No. 27, RT.01/RW.13, Kelurahan Kreo Selatan, Kecqmqtqn Larangan, Kota Tangerang, Banten. Al-Hasanah Mosque congregation is growing rapidly and DKM intends to expand the mosque building and turn it into a mosque. The current condition of the Al-Hasanah prayer room consists of a 1-story building. And the early history of this prayer room was a house belonging to the congregation which was then donated to become a prayer room. The current condition of the Al-Hasanah Mosque needs to be developed because the congregation of the Al-Hasanah Mosque is increasing and is becoming increasingly unaccommodated. Based on these conditions, Budi Luhur University Architecture Study Program organized Community Service activities to jointly prepare the Al-Hasanah Mosque Renovation Budget Plan. The method of implementing the activities uses the Architectural Design Process. Where the renovation design of the Al-Hasanah Mosque is adjusted to the input from the mosque manager, while the working drawings of the mosque renovation design are adjusted to architectural standards. Then proceed with the calculation of costs (RAB) based on the preliminary drawings that have been mutually agreed upon